Global overexpression of divalent metal transporter 1 delays crocidolite-induced mesothelial carcinogenesis in male mice. (2nd September 2018) - Funahashi, Satomi; Okazaki, Yasumasa; Nishiyama, Takahiro; Ohyoshi, Hidekazu; Yasui, Hiroyuki; Nishida, Kazuki; Matsui, Shigeyuki; Toyokuni, Shinya
Abstract: Exposure to asbestos fiber is central to mesothelial carcinogenesis, for which iron overload in or near mesothelial cells is a key pathogenic mechanism. Alternatively, iron chelation therapy with deferasirox or regular phlebotomy was significantly preventive against crocidolite-induced mesothelial carcinogenesis in rats. However, the role of iron transporters during asbestos-induced carcinogenesis remains elusive. Here, we studied the role of divalent metal transporter 1 (DMT1; Slc11a2), which is a Fe(II) transporter, that is present not only on the apical plasma membrane of duodenal cells but also on the lysosomal membrane of every cell, in crocidolite-induced mesothelial carcinogenesis using DMT1 transgenic ( DMT1 Tg) mice. DMT1 Tg mice show mucosal block of iron absorption without cancer susceptibility under normal diet. We unexpectedly found that superoxide production was significantly decreased upon stimulation with crocidolite both in neutrophils and macrophages of DMT1 Tg mice, and the macrophage surface revealed higher iron content 1 h after contact with crocidolite. Intraperitoneal injection of 3 mg crocidolite ultimately induced malignant mesothelioma in ∼50% of both wild-type and DMT1 Tg mice (23/47 and 14/28, respectively); this effect was marginally ( p  = 0.069) delayed in DMT1 Tg mice, promoting survival. The promotional effect of nitrilotriacetic acid was limited, and the liver showed significantly higher iron content both in DMT1 Tg mice and after crocidolite exposure. The results indicate that global DMT1 overexpression causes decreased superoxide generation upon stimulation in inflammatory cells, which presumably delayed the promotional stage of crocidolite-induced mesothelial carcinogenesis. DMT1 Tg mice with low-stamina inflammatory cells may be helpful to evaluate the involvement of inflammation in various pathologies.